Electronic Know Your Customer (E-KYC) Model in the Factual Verification of Political Party Membership for Electoral Integrity within an E-Government Framework: Evidence from the Indonesian Election Commission - Handi Tri Ujiono (International Journal of Social Science and Humanity, 2026)
Factual verification of political party membership constitutes a critical administrative stage in electoral management, as it directly affects electoral integrity and democratic legitimacy. In Indonesia, this process remains predominantly reliant on conventional door-to-door verification methods, which face structural constraints including time limitations, excessive administrative burden, high costs, and vulnerability to procedural errors and electoral disputes. Meanwhile, the advancement of e-government and Electronic-Based Government Systems (E-Government) has created opportunities to adopt more accountable and verifiable digital identity mechanisms. This study aims to conceptualize and examine Electronic Know Your Customer (E-KYC) as an administrative governance model for verifying political party membership to strengthen electoral integrity within an e-government framework. Employing a mixed-methods approach with a sequential explanatory design, quantitative data were collected through a survey of 44 election officials at district and municipal election commissions in Central Java Province, Indonesia. Qualitative data were obtained through in-depth interviews with key institutional actors. The findings demonstrate a positive and significant relationship between the adoption of E-KYC and strengthened administrative electoral integrity, democratic public service values, and institutional readiness. Qualitative evidence further indicates that challenges to electoral integrity stem primarily from weaknesses in administrative procedures rather than from political contestation itself. This study concludes that E-KYC should be positioned not merely as a technological innovation but as an institutionalized administrative governance model, contingent upon regulatory clarity, system interoperability, and organizational capacity building.